Development of the destination branding model based on tourism industry nostalgia - parinaz masoumi; vahidreza mirabi; jalal HaghighatMonfared; Ahmad Vedadi (ارزش آفرینی در مدیریت کسب و کار)
Abstract The main purpose of this research is to provide a destination branding model based on the nostalgia of the tourism industry, so the current research is in the field of applied-developmental research. Also, based on the nature and method, the current research is a descriptive-survey research with a mixed (qualitative-quantitative) approach, which is conducted cross-sectionally in terms of time. The statistical sample in the qualitative section includes 30 academic and market experts related to the tourism industry, which was purposefully non-random and finally reached theoretical saturation with the number of 30 semi-structured interviews. In the quantitative part, the statistical population includes all tourists of Tehran province in 1401, from which a sample of 384 people was selected. The data collection tool in the qualitative part includes a semi-structured interview and in the quantitative part it includes a questionnaire from the qualitative phase. Data analysis was done in qualitative method with database approach and MAXQDA 20 software. Validation of the model was done with partial least squares technique and SmartPLS software. Based on qualitative analysis, the paradigm model of research in six dimensions of causal factors (sometimes from the destination brand, destination brand image, tourist relationship management, tourist participation), background conditions (tourism infrastructure), intervening factors (host tourism culture), strategies (branding) based on nostalgia), central phenomenon (tourism brand development) and consequences (tourist travel decision) were designed. Based on the results obtained from the validation of the model in the quantitative section, it was determined that the proposed model of this research has adequate validity. Extended Abstract Introduction Today, tourism activity is considered as one of the most important and dynamic activities in the world, so that the number of foreign and domestic tourists and their income generation is constantly increasing at the global level. Identifying important and effective variables in the tourism industry is effective in changing the demand pattern of many countries. Therefore, tourism marketing and specifically, branding of tourist destinations has become one of the most key concepts in the field of tourism (Adachi et al, 2022). Creating a reliable tourism brand makes customers loyal to a specific tourist destination. In an age where the competition between agencies and tourism destinations has intensified more than ever, creating loyal customers has become the golden key to the success of companies active in the field of tourism (Suhartanto et al, 2022). However, the number of researches that have specifically focused on the impact of nostalgia on customer loyalty is not very high. On one hand, the relationship between nostalgia and loyalty to a tourist destination is not a linear and straightforward relationship, and undoubtedly other factors can also play a role in this relationship. Therefore, theoretical frameworks with more complexity and elegance are needed to explain the impact of nostalgia on loyalty. On the other hand, it should be kept in mind that despite the extensive domestic studies related to tourism marketing, the importance and role of nostalgia in the tourism industry has been given less attention, which explains the need to address this category. Therefore, considering the importance of the topic, the main question of the current research is, "How is the branding model based on the role of nostalgia on the tourist's travel decision in the tourism industry?" Theoretical Framework Tourism is the set of activities of people who travel to places outside the usual environment of their society; for leisure, entertainment, business or any other purpose and stay in that place for a while. The importance of tourism is due to the fact that this field is considered a dynamic, competitive and income-generating industry. A significant part of the budget of developed and developing countries is provided by the tourism industry. Many tourist countries adopt written strategic plans to improve their performance in this industry (Cheraghi et al., 2021). Some researchers have introduced tourism destinations as a complete concept with a definition; that is, destinations are places that have made a combination of tourism products and services consumed under the brand name of the destination. According to the definition of the World Trade Organization, a destination is a unique place where the visitor spends at least one night and presents tourism products such as attractions, support services and tourism resources with specific management, physical and administrative boundaries and a well-known image (Wang et al., 2022). Nostalgia can be a powerful motivator that can influence people's behavioral intention. Nostalgia is known as an internal motivation that makes a person look for a way to need to relive past experiences whose memories cause pleasurable thoughts and feelings (Jacobsen, 2023). Research Methodology The main purpose of this research is to provide a model of destination branding based on nostalgia and tourist travel decision in the tourism industry, so the current research is in the field of applicable-developmental research. Also, based on the nature and method, the current research is a descriptive-survey research with a mixed (qualitative-quantitative) approach, which is conducted cross-sectionally in terms of time. In this research, first, the initial research model was designed using the database theory, and then the obtained model (qualitative part) was subjected to validation using a field survey. The foundation data method and three stages of coding including open, central and selective coding were used to compile the initial model. The data collection tool included a semi-structured interview in the qualitative part, and a questionnaire from the qualitative phase (including 9 dimensions and 60 items) in the quantitative part. The statistical population in the qualitative section includes academic and market experts related to the tourism industry. The selection of 30 sample people was done purposefully and non-randomly, with the snowball technique. Determining the sample size in the qualitative section has been done with the number of 30 people in a semi-structured interview, based on reaching theoretical saturation. The statistical population of the quantitative research includes all tourists of Tehran province (unlimited society), which is selected using the formula of Kochran's unlimited society; a sample consisting of 384 people. Data analysis was done in both descriptive and inferential ways, and the bootstrap method was used by Smart PLS software to test the research hypotheses. The analysis in the qualitative section was done by MAXQDA 20 software. Research Findings Based on the selective coding results of the research, tourism infrastructures (including indicators of access to places of residence, transportation services of tourist destinations, access to various natural attractions, amenities and various tourism facilities) were selected as background categories in presenting the brand development model based on the role of nostalgia on the decision of the tourist trips in the tourism industry. Also, awareness of the destination brand, image of the destination brand, relationship management with tourists, and participation of tourists were identified as causal conditions in the model of destination branding based on nostalgia in the tourism industry. Tourism brand development (including tourism destination reputation indicators, tourism destination popularity, positive word-of-mouth advertising of tourism destination, etc.) were selected as the central phenomenon category in presenting the brand development model based on the role of nostalgia on the tourist's travel decision in the tourism industry. Brand nostalgia (including indicators of paying attention to emotional components and past experiences, creating cognitive and emotional connections, paying attention to the traditional culture of the tourist destination, the ideal self-concept of the tourist destination, etc.) were chosen as a category of strategies and actions in presenting the brand development model based on the role of nostalgia on the decision of the tourist travel in the tourism industry. Host tourism culture (including indicators of respect for tourists and hospitality, respect for different ethnic groups and beliefs of tourists, the spirit of accepting tourists, compliance with individual and social norms and values, etc.) were selected as a category of intervening conditions to present a brand development model based on the role of nostalgia on the tourist's travel decision in the tourism industry. Tourist travel decision (including indicators of planning to travel to a tourist destination, recommending others to travel to a tourist destination, etc.) were selected as the consequences category in presenting the brand development model based on the role of nostalgia on the tourist travel decision in the tourism industry. And finally, according to the qualitative part and the model presented using smart pls software, the relationship between the research variables, which was designed according to the model of the research assumptions, was examined and tested, and all the research assumptions were confirmed. Conclusion The results obtained in the first and second hypotheses show that brand awareness and brand image have a positive and significant impact on tourism brand development. Based on these findings, it is clear that in order to develop the tourism brand, it is necessary to provide proper information about the destination through different channels to increase people's desire to visit these areas. Also, the image that tourists keep of a tourist destination in their mind will also affect the development of the tourism brand. Research shows that people who have the desire to visit tourist destinations and buy from these destinations are more knowledgeable about tourist destinations than ordinary people. (Keskin et al., 2022). It is worth noting that in many cases it has been reported that creating a nostalgic feeling also improves the image of the tourist destination (Chi & Chi, 2022; Wang, 2022). In the third to fifth hypotheses, it was shown that nostalgia is influenced by factors such as brand development (branding), host culture, and infrastructure. As mentioned before, people feel very good about reminiscing; therefore, by inducing a sense of nostalgia in people, a big step can be taken in the direction of branding. Specifically in the field of tourism, if a tourist destination can evoke memories of the past among tourists, people's attitude towards the brand of that destination will improve significantly. Such a finding has already been reported by other researchers (Jiang, 2019; Christou, 2020). In the sixth and seventh hypotheses, it was found that the management of relations with tourists and the participation of tourists have a positive and significant effect on the development of the tourism brand. Tourist relationship management includes all the activities that a tourist center does to create a long-term relationship with customers. These communications include advertising, receiving feedback from customers, offering discounts, etc., and thus can lead to the formation of a powerful brand in the tourism market. On the other hand, branding in the modern era is a two-way relationship between the customer and the company, and without the participation of customers, the probability of success in branding decreases. Even today, the concept of value co-creation has been proposed, which shows that brand value is the result of continuous interaction between the brand and the customer, and without the participation of tourists, a strong brand cannot be created. The obtained results are consistent with the findings of previous researchers (Xu et al, 2023; Volgger et al, 2021). According to the result obtained about the effect of nostalgia on loyalty, it is suggested that tourism managers should first identify the factors that create a sense of nostalgia in tourists, and increase their intention to visit again by focusing on such factors.